2011
DOI: 10.1007/s11746-011-1873-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Glycidyl Esters of Fatty Acids in Vegetable Oils by LC–MS

Abstract: An LC–MS method using a single quadrupole mass spectrometer was developed for direct analysis of glycidyl esters of fatty acids in vegetable oils. Without any sample clean-up, this method provided acceptable recovery of seven glycidyl esters, comparable results to a previously-published method utilizing two solid-phase extraction steps, and consistent detection parameters after greater than 200 injections without any cleaning operations performed. This method could readily be implemented as a screening assay f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…The quality of indirect methodology has improved, and there are now several methods that appear to provide accurate quantitative information for these classes of contaminants (Kuhlmann 2011;Ermacora & Hrncirik 2013). As a response to the lack of reliability of the early indirect methods, direct approaches were developed for GEs (Blumhorst et al 2011;DuBois et al 2011;Firestone 2011;Haines et al 2011;Becalski et al 2012;Hori, Koriyama, et al 2012) and 3-MCPD esters (Haines et al 2011;Dubois et al 2012;Hori, Koriyama, et al 2012;Hori, Matsubara, et al 2012;Moravcova et al 2012;Yamazaki et al 2013) that do not require hydrolysis and analyse the fatty acid esters as they occur in processed oils without any structural modification. However, due to limitations with each of these direct approaches, methods were developed and validated in our laboratory at the USFDA the LC-MS/MS quantitation of intact esters of 3-MCPD and glycidol in edible oils MacMahon, Mazzola, et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The quality of indirect methodology has improved, and there are now several methods that appear to provide accurate quantitative information for these classes of contaminants (Kuhlmann 2011;Ermacora & Hrncirik 2013). As a response to the lack of reliability of the early indirect methods, direct approaches were developed for GEs (Blumhorst et al 2011;DuBois et al 2011;Firestone 2011;Haines et al 2011;Becalski et al 2012;Hori, Koriyama, et al 2012) and 3-MCPD esters (Haines et al 2011;Dubois et al 2012;Hori, Koriyama, et al 2012;Hori, Matsubara, et al 2012;Moravcova et al 2012;Yamazaki et al 2013) that do not require hydrolysis and analyse the fatty acid esters as they occur in processed oils without any structural modification. However, due to limitations with each of these direct approaches, methods were developed and validated in our laboratory at the USFDA the LC-MS/MS quantitation of intact esters of 3-MCPD and glycidol in edible oils MacMahon, Mazzola, et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A similar approach to analysis by LC-MS (single stage quadrupole) using custom made internal standards of 7 GEs was also outlined by Granvogl and Schieberle [19]. Another recent paper described single stage quadrupole LC-MS analysis of GEs in vegetable oils without any purification using D31 glycidyl palmitate as an internal standard with LOQ in the range of 200-600 μg/kg [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods to provide accurate quantification of GE are required. Blumhorst et al [9] reported a direct liquid chromatography-mass spectrometry (LC-MS) method which can be used as a screening method to quantify GE in processed oil samples. These researchers reported acceptable method recovery and repeatability, but Masukawa et al [6] reported a rapid decline in instrument signal/noise following injection of diluted oils without further clean-up.…”
Section: Introductionmentioning
confidence: 99%